Who earns trust in online environments? A meta-analysis of trust in technology and trust in provider for technology acceptance - Leonie Kuen; Daniel Westmattelmann; Maike Bruckes; Gerhard Schewe (Electronic Markets, 2023)
Trust has been identified as inevitable for technology acceptance and might further gain importance as technologies become increasingly complex. However, previous research on trust in online environments lacks a systematic configuration of trust entities in research models; some studies include either trust in technology or trust in provider, others both. In combination with inconsistent results, this leads to a lack of in-depth knowledge about the trust entities' relationship to each other, to their antecedents, and intention to use. Therefore, this study aims at clarifying these relationships and examining how they vary for different configurations. We performed pairwise meta-analyses to generate summary effects for the individual trust entities and examined four different trust configurations by applying meta-analytic structural equation modeling (MASEM). Our findings advance technology acceptance and trust research and highlight the necessity to carefully configure trust. More specifically, the results from pairwise meta-analysis support a strong relationship between the trust entities that is, however, countered by the effects of antecedents in MASEM. Institution-based trust and reputation are found stronger predictors for trust in provider and familiarity a stronger determinant of trust in technology. Furthermore, the trust entities show comparable paths to intention to use when either trust entity is included in the research model, but when both are integrated, trust in technology is more important than trust in provider.
Keywords: M31; L81; D91; 620; Trust in technology; Trust in provider; Online trust; Technology acceptance; Trust formation; Meta-analysis